Microwave synthesis and photocatalytic activities of ZnO bipods with different aspect ratios. (February 2016) - Sun, Fazhe; Zhao, Zengdian; Qiao, Xueliang; Tan, Fatang; Wang, Wei
Graphical abstract: Highlights: We synthesized linked ZnO nanorods by a facile microwave method. The effect of reaction parameters on ZnO was investigated. ZnO bipods with different aspect ratios were prepared. The photocatalytic performance of ZnO bipods was evaluated. Abstract: Linked ZnO nanorods have been successfully prepared via a facile microwave method without any post-synthesis treatment. The X-ray diffraction (XRD) patterns indicated the precursor had completely transformed into the pure ZnO crystal. The images of field emitting scanning electron microscope (FESEM) and transmission electron microscope (TEM) showed that linked ZnO nanorods consisted predominantly of ZnO bipods. The formation process of the ZnO bipods was clearly discussed. ZnO bipods with different aspect ratios have been obtained by tuning the concentrations of reagents and microwave power. Moreover, the photocatalytic performance of ZnO bipods with different aspect ratios for degradation of methylene blue was systematically evaluated. The results of photocatalytic experiments showed that the photocatalytic activity increased with the aspect ratios of ZnO bipods increased. The reason is that ZnO bipods with larger aspect ratio have higher surface area, which can absorb more MB molecules to react with OH radicals.